The Relationship Between Fast Food Consumption Habits and Physical Activity on Body Mass Index (BMI) in Adolescents at SMAN 5 Kota Jambi - Afriani, Shelly; Rudini, Dini; Sari, Yulia Indah Permata (Jurnal Pinang Masak, 2025)
Background: The prevalence of overweight and obesity among adolescents continues to increase, including in Jambi City. High consumption of fast food and low physical activity are suspected to contribute to this issue. This study aims to determine the relationship between fast food consumption habits and physical activity with body mass index (BMI) among adolescents at SMAN 5 Jambi City. This research is an analytical observational study with a cross-sectional approach. A total of 98 respondents were selected using stratified random sampling. Data were collected using the Food Frequency Questionnaire (FFQ) for fast food consumption, the Global Physical Activity Questionnaire (GPAQ) for physical activity, and BMI measurements. Data analysis was conducted using the Spearman-Rank correlation test. The majority of respondents were female (75.51%) and aged 16 years (45.92%). Most respondents had a moderate level of fast food consumption (34.69%), high physical activity (51.02%), and normal BMI. The statistical analysis showed a significant relationship between fast food consumption and BMI (r = 0.32; p = 0.001) with a weak positive correlation. Meanwhile, no significant relationship was found between physical activity and BMI (r = -0.13; p = 0.216). There is a significant relationship between fast food consumption and BMI, while no significant relationship was found between physical activity and BMI among adolescents at SMAN 5 Jambi City.